A Comparative Phytochemical Analysis Of Bougainvillea Glabra Choisy And Calforina Gold - NEHA SAHU,; DR. JYOTI SAXENA, (International Journal of Pharma and Bio Sciences, 2012)
The present study was undertaken to find out the phytochemicals present in Bougainvillea glabra flowers extract and comparative study between B.glabra ‘choisy’ and B. glabra ‘califorina gold’. Fresh flowers and bracts of botanically identified plant was collected and were processed for preparation of plant extract using specified technique.The plant extract was then subjected for different qualitative chemical tests to investigate the chemical profile of B.glabra extracts. Analysis showed the presence of alkaloids, Flavonoids, phenolic compounds and tannins in the extact as confirmed by implying different qualitative tests specified for these phytochemicals.